ความผันแปรทางกายวิภาคตามทางผ่านของเส้นประสาท suprascapular: Variations in Anatomy Along the Course of the Suprascapular Nerve - Putiwat, Phongpitak; Kumchantuek, Tewarat (Asian Health, Science and Technology Reports, 2010)
The objective of the study is to investigate the pathway of suprascapular nerve, the shape of suprascapular notch, and the suprascapular ligament of eighty upper limbs of twenty-three to ninety-two-year-old cadavers. According to the study, the percentages of the suprascapular nerve that passes inferior and superior to the suprascapular ligament are 95 % and 5 % respectively. The part of the nerves that passes superior to the suprascapular ligament found in males only. The shape of the suprascapular notch can be divided into two features which are U and V shapes and both sides of all suprascapular ligament are U-shaped more than V-shaped. The shapes of suprascapular notch: U-shape and V-shape, are 71.25% and 28.75% respectively. And the figures of suprascapular ligament: Fan-shape and Cord-shape, are 55% and 45% respectively. Likewise, only 2.35% of suprascapular ligament shows the accumulation of calcium which became bones. Regarding the database taken from the study, suprascapular nerve entrapment syndrome can be diagnosed especially among athletes of volleyball, tennis, and baseball.